Communications and Positioning by Satelhte in the International Road Transport System - Marin, Draško (Promet - Traffic&Transportation, 2012)
This article describes the basic technology of satellite .I)’Stemsrelated to the geostationary satellites particular(v with regardto the .)’Stem of satellites in the European network ofEUTELSAT (European Telecommunications Satellite Organization)covering Europe, North Africa and part of the MiddleEast.This enables positioning of vehicles in the internationalroad transport system in the territory which has been covered bythe satellite signal.The EUTELTRACS system within the EUTELSAT organizationenables not only positioning with preciseness ofabout 300 m, but also two-way communications between vehiclesand company headquarters, which is an advantage comparedto the other positioning systems.EUTELTRACS service belongs to the land mobile satelliteservices with secondary status (it must not impose any interferenceto other radio-communication services and cannot claimprotection from other services).The use of frequency bands is for the up-links 14.0-14.25GHz, and for the down-links 10.25-11.20 GHz, 11.45-11.70GHz and 12.50-12.75 GHz.The EUTELTRACS system provides services by means ofOmniTRACS terminals and CEPT (European Conference ofPostal and Telecommunications Administrations) administrationsissue type approvals, designating the terminal markingand make decisions regarding free circulation of terminals inconformity with their national regulations.The OmniTRACS terminal.l)’stem has been specially presentedas well as the fixed part of EUTELTRACS .)’Stem withthe satellite segment.Every transport company has been considered as a subscriberto an authorised EUTELTRACS service provider.The service for tracing trucks in the international trafficthroughout Europe and Middle East can be fully expressed byincluding the stronger transport companies (more than 10trucks) which can establish the transport more rationallythrough EUTELTRACS service.The implementation of the EUTELTRACS service hasbeen imposed on the Croatian companies, whose internationaltransport could be well developed.Croatia has been a member of the EUTELSAT organisationsince December 1992, and this has provided the basic conditions for organising this service. The service provider canbe the acting telecommunications operator, in this case theCroatian Post and Telecommunications (HPT), or any othercompany in co-operation with HPT (leasing the telecommunicationslines, tariffs, maintenance etc.).The article presents the possibility of implementing theEUTELTRACS service in Croatia with the responsibility of theservice provider to establish connections between any dispatchcentre in Croatia by means of Croatian telecommunicationsnetwork, and through international network to the HUB stationand the corresponding geostationary satellites, includingthe accounting matters.It also presents the usage of the computerised road maps foraccurate vehicle position-plotting and free circulation for OmniTRACSterminals.